Cellular and Molecular Mechanisms in Neurodegenerative Disorders: A Comprehensive Scoping Review - Meneses Rêgo, Amalia Cinthia; Araújo-Filho, Irami (International Journal of Innovative Research in Medical Science, 2024)
This scoping review aimed to systematically map the current literature on cellular and molecular mechanisms involved in neurodegenerative disorders, including Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis (ALS), and frontotemporal dementia. The primary objectives were to identify critical research areas, highlight existing knowledge gaps, and suggest directions for future studies. Following PRISMA-ScR guidelines, studies were selected based on predefined inclusion criteria, focusing on recent (last five years) original research, systematic reviews, meta-analyses, and clinical trials published in peer-reviewed journals. Comprehensive searches were conducted across multiple databases, such as PubMed, EMBASE, Cochrane Library, Scopus, and Web of Science, alongside grey literature from Google Scholar. Key findings demonstrated that mechanisms such as protein aggregation, mitochondrial dysfunction, oxidative stress, neuroinflammation, and dysregulation of cellular degradation pathways are fundamental in the pathogenesis of neurodegenerative diseases. The review identified significant gaps, particularly in understanding how these mechanisms interact and contribute to disease progression, suggesting a critical need for integrated, multi-targeted therapeutic strategies. This synthesis provides a foundation for future research efforts to develop targeted therapies and improve patient care.